Analyzing Various Existing Security Techniques to Secure Data Access in Cloud Environment - Jain, Rachna; Madan, Sushila; Garg, Bindu (International Journal of Computer Sciences and Engineering, 2015)
Cloud computing is the key powerhouse in numerous organizations due to shifting of their data to the cloud environment. The use of cloud computing has been increased rapidly in various organizations as it provides multiple benefits in terms of low cost and accessibility of data. There are different types of issues have been observed in cloud computing environment that need to be addressed. In the past, International Data Corporation (IDC) conducted a survey of 263 IT executives to gauge their opinion about the usage of IT cloud services in companies. As a result, Security was ranked first and observed utmost issue of cloud computing. So nowadays, protection of data in cloud is a big deal. Organizations mislay control over the data as soon as data moves to the cloud. Thus, protection needed to secure data is directly proportional to the value of the data.The first level of security where cryptography can help cloud computing is secure storage .There are already some cloud providers that have started providing secure storage services but offering different levels of protection.The major handicap of secure storage is that we cannot outsource the processing of this data without decrypting it before or without revealing the keys used for encryption. In this paper, various techniques to secure data access in cloud environment has been analyzed and during analysis it is observed that security need to be addressed for securing transaction in such a way that transaction should be encrypted and not be decrypted during access. Moreover, access should be provided to the users as per their access rights. Security can be enhanced by use of multi cloud as single cloud that become less popular with customers due to risks of service availability failure and the possibility of malicious insiders in the single cloud.